A molecular timescale for evolution of cobamide biosynthesis - Jichen Wang; Chao Ai; James M. Tiedje; Yuan Ge (Proceedings of the National Academy of Sciences, 2026)
Cobamides are essential nutrients for most organisms but are only biosynthesized by a limited number of taxa through aerobic and anaerobic pathways. Although the origin of these widespread shared cofactors changed ecosystems and the metabolisms of living organisms, little evolutionary information is available about the biosynthetic genes and the producers. Here, we established a timeframe for the emergence of cobamide biosynthesis genes and producers, using a series of Bayesian molecular clock analyses combined with phylogenetic reconciliation. We revealed the partial producers of tetrapyrrole precursor and corrin ring were earlier than the oldest cobamide producer, suggesting the possibility that cobamide-like compounds may have existed before the emergence of their de novo producers. We also found that the anaerobic de novo producers and corrin ring producers emerged first ( Pelobacter , around 2458 Mya), and that the Great Oxidation Event postdated emergence of aerobic producers ( Kribbella , around 1784 Mya). These findings reveal the chronology of cobamide biosynthesis, which greatly changed global ecological frameworks and resulted in the current biosphere, and can guide the exploration of cross-feeding and the origin of diverse organisms on the planet.